African Disability Rights Yearbook Volume 7 2019
The African Disability Rights Yearbook aims to advance disability scholarship. Coming in the wake of the United Nations Convention on the Rights of Persons with Disabilities, it is the first peer-reviewed journal to focus exclusively on disability as human rights on the African continent. It provides an annual forum for scholarly analysis on issues pertaining to the human rights of persons with disabilities. It is also a source for country-based reports as well as commentaries on recent developments in the field of disability rights in the African region.